PENERAPAN TEKNIK MEMBACA DALAM HATIUNTUK MENINGKATKAN KEMAMPUAN MENCARI GAGASAN POKOKKARANGAN NARASI ANAK SISWA KELAS IVSD NEGERI 012 PAGARAN TAPAH DARUSSALAM - Suriaman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on the research that has been conducted, it was concluded that the ability of fourth-grade students of SD Negeri 012 Pagaran Tapah Darussalam to identify key ideas can be improved through silent reading techniques. This is evident from the increase in students’ ability to find key ideas from before the implementation of the silent reading technique to the second cycle of the second meeting. The preliminary data showed that the average student score was 61.4. In terms of classical completeness, only 14.3% of students (2 students) achieved the minimum score of 65 according to the KKM standard. At the first meeting of the first cycle, the class average increased to 66.4, with 50% of students (7 students) achieving completeness. At the second meeting, the average score rose to 70.7, with 57.1% of students (8 students) achieving completeness. These results indicate improvement and show that the research was successful. At the first meeting of the second cycle, the class average increased again to 74.3, with 78.6% of students (11 students) achieving completeness. Finally, at the second meeting of the second cycle, the average score reached 81.4, with 100% of students (14 students) achieving classical completeness.